Prevalence and associated factors of geriatric depression among institutionalised senior citizens: a cross-sectional study - Xavier, Mary Ancy N.; Vathathu Krishnan, Usha (International Journal Of Community Medicine And Public Health, 2024)
Background: Ageing is an inevitable process. As a result of empty nest syndrome, the senior citizens of Kerala, are forced for institutionalization. Prevalence of mental morbidity among institutionalized senior citizens outnumbers those living in families. Depression is one of the most common psychiatric morbidities among senior citizens. The present study aims to determine the prevalence and factors associated with geriatric depression among institutionalized senior citizens of Ernakulam district. Methods: A cross-sectional descriptive study was conducted over a period of 3 months among 238 institutionalised senior citizens aged 60 years and above using geriatric depression scale- short form (GDS-SF). Data was entered and analysed using SPSS. Results: Among participants, 23.11% reported mild depression, 4.20% had moderate and 7.14% had severe depression. Chi-square test was used to study the association of various factors with geriatric depression. Previous employment status, source of income, frequency of visit by relatives, contact with relatives through phone, duration of leisure time activities and sleep quality showed a statistically significant association. Conclusions: The study highlights the need for regular screening activities. Further research is necessary on identification of modifiable risk factors.